Fast and slow optical rogue waves in the fiber laser - Kbashi, Hani J.; Kolpakov, S. A.; Sergeyev, Sergey V. (Frontiers in Physics, 2022)
We report an experimental study of fast and slow temporal scaling of rogue waves' emergence in a long (615 m) ring cavity erbium-doped fiber laser. The criteria for distinguishing between the fast and slow rogue waves is a comparison of the event lifetime with the system's main characteristic time estimated from the decay of an autocorrelation function (AF). Thus, compared with AF characteristic time, fast optical rogue wave (FORW) events have a lifetime duration shorter than the AF decay time and appeared due to the mechanism of pulse-to-pulse interaction and nonlinear pulses dynamics. In contrast, a slow optical rogue wave (SORW) has a lifetime duration much longer than the decay time of the AF, which results from the hopping between different attractors. Switching between regimes can be managed by adjusting the in-cavity birefringence.